PELATIHAN MS OFFICE SEBAGAI PENUNJANG KEGIATAN ADMINISTRASI APARAT KAMPUNG ONGGARI DISTRIK MALIND - Agus Prayitno; Syaiful Nugraha (Musamus Devotion Journal, 2023)
The use of information technology, especially computer programs, is nowadays very beneficial to work efficiency. A person's ability to use MS Office programs such as Microsoft Word, Excel and Powerpoint will speed up the village's tools to accomplish tasks by Specifically related to administration with more and more village tools controlling these applications so that they have more time needed because they can do it on their own and without the help of other parties. Once simple documentation was created, this training was aimed at Onggari village officials in Malind County with the aim of enabling village officials to develop their abilities or skills by proficiently using computer programs and making the most of them. To carry out activities related to information management in the Onggari Village District.